Correlation of reading ability with achievement in science and in mathematics among fourth year students in the Manila general public high schools - Gomez, Consuelo S. (Tukay) 1928- (1963)
The primary purpose of the study was to determine whether reading ability could predict scholastic success in science and in mathematics. The Philippine Achievement Test, Series B (Reading), Form III, Test on Interpretation of Literary Materials, Test on Mathematical Ability and the Philippine Achievement Test in Science were given to a random sample of forty-eight fourth year students in the public general high schools in 1960, who had equated background in science and in mathematics.
Thesis (M.A. Education)--University of the Philippines, Diliman.
Keywords: Reading; Mathematics -- Study and teaching (Secondary).; Science -- Study and teaching (Secondary).